Odpowiedzi

2010-03-22T16:21:36+01:00
4x-6y+2=0
3x+y=x+11

4x=6y-2 /÷4
3x+y=x+11

x=1,5y-0,5
3(1,5y-0,5)+y=1,5y-0,5+11

x=1,5y-0,5
4,5y-1,5+y=1,5y+10,5

x=1,5y-0,5
4y=12 /÷4

x=1,5y-0,5
y=3

x=1,5*3-0,5
y=3

x=4
y=3
1 5 1
2010-03-22T16:24:14+01:00
4x-6y+2=0
3x+y=x+11

4x-6y=0-2
3x+y-x=11

4x-6y=-2
2x+y=11/*6

4x-6y=-2
12x+6y=66

16x=64/:16
x=4

4x-6y=-2
4*4-6y=-2
16-6y=-2
-6y=-2-16
-6y=-18/:(-6)
y=3
2010-03-22T16:25:47+01:00
4x-6y+2=0/-2
3x+y=x+11/-3x

4x-6y=-2
y=-2x+11

4x-6(-2x+11)=0
y=-2x+11

16x-66=0/+66
y=-2x+11

16x=66/:16
y=-2x+11

x=4,125
y=-2*4,125+11

x=4,125
y=-8,25+11

x=4,125
y=2,75